Ex-post evaluation of the impact of restructuring aid decisions on the viability of aided (non-financial) firms: Final report - Directorate-General for Competition (Brussels) European Commission (European Commission, Directorate-General for Competition, 2016)
Financial distress and market exit play a key role in ensuring an efficient allocation and may also have negative social and economic consequences like loss of employment and output in particular areas, loss of technical knowhow and expertise or disruption to important services. In this context, State aid for the rescue and restructuring aid of firms in difficulty is a policy tool that may, in certain circumstances, be appropriate to address the negative consequences of financial distress. However, there are a number of costs associated with rescue and restructuring aid which imply that its use is only appropriate under strictly limited circumstances. Therefore, the Commission allows state aid to firms in difficulty only under strict conditions. The purpose is to evaluate whether, in its ex-ante assessment of the restructuring plans submitted by the Member States, the Commission is effective in achieving the objective of ensuring that restructuring aid (rescue aid is excluded from the scope of the project) is granted only if a restructuring plan is likely to return the firm to long-term viability within a reasonable period of time. Within an international project team ZEW will conduct the econometric analysis. – – Zahlungsschwierigkeiten und Marktaustritte spielen für die Sicherstellung einer effizienten Allokation eine wesentliche Rolle. Sie können negative soziale und ökonomische Folgen nach sich ziehen und den Verlust von Arbeitsplätzen und Produktion in bestimmten Gebieten, einen Verlust von aufgebautem technischem Know-How oder Unterbrechungen wichtiger Dienstleistungen verursachen. Vor diesem Hintergrund stellt die staatliche Beihilfe zur Rettung und Umstrukturierung in Not geratener Firmen ein Politikinstrument dar, das unter bestimmten Umständen die negativen Folgen von in finanzielle Schwierigkeiten geratenen Unternehmen auffangen kann. Die Gewährung staatlicher Beihilfen zur Umstrukturierung und Rettung ist jedoch auch mit einigen Kosten verbunden, was dazu führt, dass ein solcher Markteingriff nur unter besonderen Bedingungen sinnvoll ist. Aus diesem Grund genehmigt die Europäische Kommission staatliche Beihilfen nur wenn strenge Anforderungen erfüllt sind. Ziel der Studie ist es zu evaluieren, ob die Kommission bei ihrer ex-ante Bewertung effektiv dabei ist, staatliche Beihilfen zur Umstrukturierung von Unternehmen (Rettungsbeihilfen sind nicht Gegenstand der Studie) nur dann zu gewähren, wenn die von den Mitgliedsstaaten eingereichten Restrukturierungspläne mit großer Wahrscheinlichkeit eine wirtschaftliche Gesundung der angeschlagenen Unternehmen ermöglichen. Innerhalb des internationalen Projektteams ist das ZEW dabei für die ökonometrischen Analysen zuständig.
Keywords: 330; Corporate restructuring; Organizational change; Subsidy; Allocation; Unternehmenssanierung; Organisatorischer Wandel; Subvention; Allokation